DETERMINANTS OF BANK PROFITABILITY IN ASEAN EMERGING MARKET - GESANG, BANGUN B1024161023 (Jurnal Manajemen Update, 2020)
ABSTRACTOne of the company's goals is to achieve maximum profit. One of the efforts to reach agreement, the company must always support various strategies to maximize profits. The survival of a company is involved by many things including the profitability of the company itself. Therefore, this study discusses the factors that affect the profitability of banks in developing countries in ASEAN. This study uses 10 banks with the largest assets in Indonesia, 10 banks with the largest assets in Malaysia, and 10 banks with the largest assets in Thailand, overall this study uses 30 companies in ASEAN with a duration of 10 years. return on assets (ROA) is the dependent variable to measure bank profitability, while the independent variables used are non-performing loans (NPL), capital adequacy ratios (CAR), total assets (Size), loan-to-deposit ratio (LDR), domestic product growth gross (GDP growth), inflation, interest rates and exchange rates. These data will be processed using panel data regression with the Cochrance Orcutt method on the basis of the Fixed Effect Model. The final results of this study The results of the results are different in each country. In Indonesia only NPLs have a significant significance of ROA, which is a significant negative. In Malaysia, only the exchange rate is significant to ROA, which is a significant negative. In Thailand, only NPI has a significant effect on ROA, which is a significant negative. Overall in Southeast Asia, only NPLs, interest rates and exchange rates significantly affect ROA, which is a significant negative. In other independent variables, it do not have a significant effect on ROA. Keywords: Return on Assets (ROA), Non-performing Loans (NPL), Capital adequacy ratio (CAR), total assets (SIZE), GDP growth, Inflation, Interest Rates, and Exchange rates.  References A Suryaman, N. L. (2017). Determinats of Banking Company Stock Price.Abreu, M. a. (2001). Commercial bank interest margins and profitability: Evidence for some EU countries.Achmad, M. D. (2005). Good Corporate Governance: Konsep dan Penerapannya dalam Konteks Indonesia. Jakarta: Ray Indonesia.Adi Nugroho, R. d. (2012). Faktor Faktor Yang Mempengaruhi Kemauan untuk membayar Pajak dengan Kesadaran membayar pajak.Agus Harjito, M. (2009). Manajemen Keuangan (1st ed.). Yogyakarta: Ekonisia.Al-Jafari, M. K. (2014). Determinants of bank profitability: Evidence from Syria. Journal of Applied Finance and Banking.Alshatti, A. S. (2015). The Effect of the Liquidity Management on Profitability in the Jordanian Commercial bank. International Journal of Business and Management.Arinta, M. F. (2015). Pengaruh Capital Adequacy Ratio (CAR) dan Loan to Deposit Ratio (LDR) Terhadap Profitabilitas perusahaan perbankan yang terdaftar di Bursa Efek Indonesia tahun 2011-2013.ASSOCIATION OF SOUTHEAST ASIAN NATION. (n.d.). Retrieved 10 28, 2019, from https://asean.org/Boediono. (1996). EKonomi Moneter. Yogyakarta.Boitan, L. A. (2015). Determinants of Sustainable Banks’ profitability. Evidence from EU Countries.Buchory, H. A. (2015). Determinant of Banking Profitability in Indonesian Regional Development Bank.Budisantoso, T. d. (2014). Bank dan Lembaga Keuangan Lain. Jakarta: Salemba Empat.Catur F. Ukhriyawati, T. R. (2017). The Influence of Asset structure, Capital Structure, Risk Management and Good Corporate Governance on Financial Performance and Value of the firm through Earnings and Free Cash Flow as an Intervening Variable in Banking Companies listed in IDX.Cresswell, J. W. (2003). Research Design Qualitative, Quantitative and Mized Methods Approach . United States: Sage Publication.Dahl, R. a. (2003). Non-performing loan and terms of credit of public sector.Darmawi, H. (2011). Manajemen Perbankan. Jakarta: Bumi Aksara.Dendawijaya. (2003). Manajemen Perbankan. Jakarta: Ghalia Indonesia.Dendawijaya, L. (2009). Manajemen Perbankan. Jakarta: Ghalia Indonesia.Fahmi, I. (2012). Analisis Laporan Keuangan (2nd ed.). Bandung: Alfabeta.Goddard, J. P. (2004). The profitability of European banks: A cross-sectional and dynamic panel analysis.Greuning, B. (2011). Manajemen Perbankan. Jakarta: Bumi Aksara.Gujarati, D. (2003). Basic Econometric Fourth Edition (4th ed.). New York: McGraw-Hill.Güngör, H. (2007). Emotional Satisfaction of Customer Contacts. Amsterdam University Press.Hamonangan Siallagan, M. M. (2006). Mekanisme Corporate Governance, Kualitas Laba dan Nilai Perusahaan. Padang.Harry P. Panjaitan, D. P. (2016). Pengaruh Tingkat Kesehatan Bank dengan menggunakan Metode RGEC terhadap Harga Saham di Bank Umum yang tercatat di BEI.Hidayati, A. N. (2014). Pengaruh Inflasi, BI rate, dan Kurs terhadap Profitabilitas Bank Syariah di Indonesia .Hyde, K. (2000). Recognising Deductive Processes in Qualitative Research. Qualitative Market Research.Ika, F. a. (2013). Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur di Bursa Efek Infonesia. Value Added, 9.Joel G. Siegel, J. K. (1999). Kamus Istilah Akuntansi. Jakarta: Elex Media Komputindo.Jogiyanto. (2010). Metodologi Penelitian Bisnis. Yogyakarta: BPFE.Kardius, K. C. (2016). Produktivitas, Likuiditas dan Pengaruhnya terhadap profitabilitas bank umum dan syariah di Indonesia.Karim. (2007). Bank Islam: Analisis Fiqih dan Keuangan Edisis. Jakarta: PT Raja Grafindo Persada.Kasmir. (2008). Bank dan Lembaga Keuangan lainnya. Jakarta: PT RajaGrafindo Persada.Kasmir. (2014). Analisis Laporan Keuangan (1st ed.). Jakarta: PT Raja Grafindo Persada.Latumaerissa, J. R. (1999). Mengenal Aspek Aspek Operasi Bank Umum. Jakarta: Bumi Aksara.Linda Dwi Rosita, N. A. (2017). Banking Subsector: Performance ratio influence to Bank's stock prices during the period 2010-2014.Malhotra, N. (2014). Basic Marketing Research. England: Pearson Education.Minow, M. R. (1003). Corporate Governance (3rd ed.). Blackwell.Molyneux. (1992). Determinants of European Bank profitability.Munawir. (2002). Analisis Informasi Keuangan. Yogyakarta: Liberity Yogya.Munawir. (2010). Analisis Laporan Keuangan. Yogyakarta: Liberty Yogyajarta.Myers, S. a. (1984). Corporate Financing and Investment Decision When Firm Have Information that Investor do not have. Journal of Finance Economics.Nachrowi, N. D. (2006). Pendekatan Populer dan Praktis Ekonometrika untuk Analisis Ekonomi dan Keuangan. jakarta: LPFE.Newbold, P. C. (2003). Statistics for Business and economics. New Jersey: Pearson Education.Ni Putu Lilis Indriani, S. K. (2016). Pengaruh Variabel Tingkat Kesehatan Bank Terhadap Harga saham Perbankan di BEI.Nisar. (2015). Determinants of Bank’s Profitability in Pakistan: A latest panel data evident .Norman. (2015). The effect of Bank Specific and Macroeconomic Determinants of Banking Profitability: A study on Bangladesh .Pohan, A. (2008). Potret Kebijakan Moneter Indonesia. Jakarta: PT. Raja. Grafika Persada.Pryanka J.V Polii, I. S. (2014). Rasio Keuangan Pengaruhnya Terhadap Harga Saham Pada Bank Umum Swasta Nasional Devisa yang Go Public di BEI.Putu Wira Hedrayana, G. W. (2015). Pengaruh Komponen RGEC pada Perubahan Harga Saham Perusahaan Perbankan di BEI.Retnasih, N. R. (2016). Pengaruh Tingkat Kesehatan Bank Terhadap Harga Saham Pada Bank Pemerintah dan Swasta di BEI.Ridwan, D. (2010). Manajemen Keuangan . Jakarta.Rossazana Ab-rahim, N. K.-C.-L. (2018). CAMEL analysis on Performance of ASEAN Public listed Banks. International Business Research, 11(4).Sahara, A. Y. (2013). Analisis Pengaruh Inflasi, Suku Bunga BI, dan Produk Domestik Bruto Terhadap Return on Asset Bank Syariah di Indonesia. Jurnal Ilmu Manajemen.Saptorini Dyah Lestari, S. B. (2015). Pengaruh Capital, Asset, Earning, dan Liquidity Terhadap Harga Saham.Sartono, A. (2008). Manajemen Keuangan dan Teori Aplikasi. Yogyakarta: BPFE.Saunders, M. L. (2009). Research Methods for Business Students (5th ed.). England: Pearson Education.Septyanawati, T. A. (2014). Analisis Pengaruh Rasio keuangan Terhadap harga Saham Pada Perusahaan Manufaktur Sektor Otomotif yang Terdaftar di Bursa Efek Infonesia.Shrestha, P. a. (2016). Impact of Liquidity on Bank Profitability in Nepalese Commercial Banks .Suad, H. (1996). Manajemen Keuangan Teori dan Penerapan (Keputusan Jangka Panjang) (4th ed.). Yogyakarta: BPFE.Sukrino, S. (2003). Pengantar Teori Mikro Ekonomi. Jakarta: PT Selemba.Sularto, A. M. (2007). Pengaruh Ukuran perusahaan, profitabilitas, leverage dan Tipe Kepemilikan Perusahaan Terhadap Luas Voluntary Disclosure Laporan Keuangan Tahunan.Sutrisno. (2003). Manajemen Keuangan. Yogyakarta.Syamsudin, L. (2000). Manajemen Keuangan Perusahaan. Jakarta.Tandelilin, E. (2001). Analisis Investasi dan Manajemen Portofolio. Yogyakarta: BPFE.Taswan. (2010). Manajemen Perbankan Konsep, Teknik, dan Aplikasi. Yogyakarta.Triyono. (2008). Analisis Perubahan Kurs Rupiah terhadap Dollar Amerika.Wedari, L. K. (2004). Analisis Pengaruh Proporsi Dewan Komisaris dan Keberadaan Komite Aduit Terhadap Aktivitas Management Laba. Simposium Nasional Akuntansi.Widarjono. (2007). Teori dan Aplikasi Untuk Ekonomi dan Bisnis. Yogyakarta: Ekonosia.Williams, C. (2007). Research Methods. Journal of Business & Economics Research.Winarno, S. a. (2007). Kamus Besar ekonomi. Jakarta: Pustaka Grafika.Wismayanto, S. D. (2013). Pengaruh NPL, LDR, ROA, ROE, NIM, BOPO, dan CAR terhadap Harga Saham pada Perbankan di BEI.Wismayanto, S. D. (2013). Pengaruh NPL, LDR, ROA, ROE, NIM, BOPO, dan CAR Terhadap Harga Saham Pada Perbankan di BEI.Wolk, e. a. (2001). Singaling Agency Theory, Accounting Policy Choice. Accounting and Business Research, 18.Zikmund, W. G. (2010). Business Research Methods. United States.